PENGARUH PENGGUNAAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) TERHADAP HASIL BELAJAR MATEMATIKA DI SMA HANG TUAH 1 JAKARTA - Riska Wahyu Ananda; Slamet Soro (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Based on the results of observations by researchers at Hang Tuah 1 High School Jakarta, several problems were found in the mathematics learning process, namely the E-LKPD had not been used by teachers at Hang Tuah 1 High School Jakarta. Thus, researchers are encouraged to fulfill research with the following topics: Effects of Using Electronic Student Worksheets (E-LKPD) on Mathematics Learning Outcomes. This study used quantitative research with experimental techniques with the aim of knowing the effect of using Electronic Student Worksheets on mathematics learning outcomes at Hang Tuah 1 High School Jakarta. There were 78 students, including 39 students from class X-3 and 39 students from class X-5 who were used as samples of this study. Class X-3 as an experimental class is taught using the Electronic Student Worksheet. In contrast, class X-5 as the control class was taught using Student Worksheets and was used as a research sample. The results of this study's data analysis show t.count = 4.501615253 > t.table = 1.66515, which means that there is an influence on the Electronic Student Worksheets regarding relevant mathematics learning outcomes. Therefore, it can be concluded that the use of Electronic Student Worksheets has a positive and significant effect on mathematics learning outcomes